Keunikan Rumah Tradisional Jepang Minka - Budi Mulyadi (Diponegoro University, 2019)
(Title: The uniqueness of Japanese traditional house minka). The main goal of this research is to know everything about the Japanese traditional house minka and it's uniqueness. This research is a combination of library research and field research. The step method used in this research is observation, classification, analysis, interpretation and description. From the result of this paper, in general, can be described that the Japanese traditional house minka has a long story of development and has a uniqueness which describes the Japanese culture which is concentrated with natural and religious elements.